Mixed Mode I-II Fracture Path and Initiation Angle of Concrete at Mesoscale Level - Guodong Li; Zhengyi Ren; Zhiyuan Wang; Jiangjiang Yu; Zhimeng Zhao (Advances in Materials Science and Engineering)
This paper presents the mesolevel numerical simulation and experimental verification of mixed mode I-II fracture for the four-point shearing beam with a single-side notch based on the concrete damaged plasticity (CDP) method and the Monte Carlo simulation (MCS) random aggregate method. And it discusses the influence of volume rate and maximum size of the coarse aggregate on the fracture path and the initiation angle of concrete mixed mode I-II fracture. The results show that the coarse aggregate has a significant influence on the distribution width, average length, and the dispersion degree of the fracture path, the distribution of which can be fitted by a normal distribution function. Also, the distribution width of the fracture path has a quadratic function relationship with the height along the failure direction. The distribution of coarse aggregates at the top of the reserved notch also has a significant influence on the initiation angle, which determines the initiation crack direction of mixed mode I-II fracture in concrete. The initiation angle distributes near the failure direction and follows a normal distribution function.